Exploring Effects of C. elegans Protective Natural Microbiota on Host Physiology - Kissoyan, Kohar Annie B.; Peters, Lena; Giez, Christoph; Michels, Jan; Pees, Barbara; Hamerich, Inga K.; Schulenburg, Hinrich; Dierking, Katja (Frontiers in Cellular and Infection Microbiology, 2022)
The Caenorhabditis elegans natural microbiota was described only recently. Thus, our understanding of its effects on nematode physiology is still in its infancy. We previously showed that the C. elegans natural microbiota isolates Pseudomonas lurida MYb11 and P. fluorescens MYb115 protect the worm against pathogens such as Bacillus thuringiensis (Bt). However, the overall effects of the protective microbiota on worm physiology are incompletely understood. Here, we investigated how MYb11 and MYb115 affect C. elegans lifespan, fertility, and intestinal colonization. We further studied the capacity of MYb11 and MYb115 to protect the worm against purified Bt toxins. We show that while MYb115 and MYb11 affect reproductive timing and increase early reproduction only MYb11 reduces worm lifespan. Moreover, MYb11 aggravates killing upon toxin exposure. We conclude that MYb11 has a pathogenic potential in some contexts. This work thus highlights that certain C. elegans microbiota members can be beneficial and costly to the host in a context-dependent manner, blurring the line between good and bad.